Pilot Implementation of Falsified Medicines Directive in Hospital Pharmacy to Develop Best Practices for Medicine Decommissioning Process - Piotr Merks; Damian Świeczkowski; Mikołaj Zerhau; Anna Gawronska; Anna Kowalczuk; Klaudiusz Gajewski; Ralf Däinghaus; Miłosz Jaguszewski; David Brindley (MDPI AG, 2020)
Background: The introduction of a medicines verification and decommissioning system into the hospital pharmacy may result in an increased workload for pharmacy staff. The pilot implementation allows us to understand all the implications of the process, optimize process workflows, and estimate the time and cost of implementation. Methods: All the packages received at the hospital pharmacy had a 2D data matrix codes and were scanned. We analyzed the time needed to unpack a variety of products, scan them, and receive the notification. Results: In total, 144 packages were scanned at an average time of 3.05 s, with most (86.9%) under 4 s. Manual decommissioning using handheld scanners was less efficient than the automated solution tested and resulted in an additional 0.4 full-time equivalent hours per million packages per year. The pattern and total time of manual scanning depended not only on the quantity but also the size of the package and type of packing. Conclusions: This evaluation of scanning performance allows optimizing the process at operational, technical, and resource levels for medicine verification and decommissioning.